Pengaruh ekspor, impor, dan inflasi terhadap nilai tukar rupiah di Indonesia - Ribka BR Silitonga; Zulkarnain Ishak; Mukhlis Mukhlis (Jurnal Ekonomi Pembangunan, 2017)
Indonesia as a country rich in natural resources should have better international trade performance in improving exchange rates. This study aims to investigate the effect of exports, imports, and inflation on the rupiah exchange rate in Indonesia during 2006-2017. The data used is secondary data sourced from Bank Indonesia and the Ministry of Commerce of the Republic of Indonesia. The method used is a quantitative approach by applying multiple linear regression models. The findings of this study indicate that exports, imports have a significant negative effect on the rupiah exchange rate. While inflation has no effect on the rupiah exchange rate in Indonesia.